Mapping Internet Celebrity on TikTok: Exploring Attention Economies and Visibility Labours - Abidin Crystal (Cultural Science)
With its rapid uptake among young people around the world, it is no surprise that TikTok is buzzing with cultures and practices of internet celebrity. Most notably, the platform is becoming more commercial and professionalized with the rise of TikTok Influencers, advertising networks, and agencies dedicated to monetizing content and embedding advertising on TikTok, and top TikTok Influencers raking in millions in income annually. However, little is known about the constitution of internet celebrity on TikTok yet, and existing models of internet celebrity on predecessor apps like Instagram and YouTube do not neatly apply to the distinctive terrain of TikTok. As such, this paper is an exploratory study into the makings of internet celebrity cultures on TikTok, focused on how attention economy and visibility labour practices have emerged as a result of the app’s features. With empirical data drawn from an extended period in-depth digital ethnography, and analyses and insights informed and supported by traditional anthropological participant observation and personal interviews with TikTok Influencers and agencies, this scoping paper offers a foundation for how celebrity, attention, and visibility are constituted across TikTok’s platform norms and features.